Assessment of the in vivo biofunctionality of a biomimetic hybrid scaffold for osteochondral tissue regeneration. Issue 1 (9th October 2020) - Tschon, Matilde; Brogini, Silvia; Parrilli, Annapaola; Bertoldi, Serena; Silini, Antonietta; Parolini, Ornella; Faré, Silvia; Martini, Lucia; Veronesi, Francesca; Fini, Milena; Giavaresi, Gianluca
Abstract: Chondral and osteochondral lesions represent one of the most challenging problems in the orthopedic field, as these types of injuries lead to disability and worsened quality of life for patients and have an economic impact on the healthcare system. The aim of this in vivo study was to develop a new tissue engineering approach through a hybrid scaffold for osteochondral tissue regeneration made of porous polyurethane foam (PU) coated under vacuum with calcium phosphates (PU/VAC). Scaffold characterization showed a highly porous and interconnected structure. Human amniotic mesenchymal stromal cells (hAMSCs) were loaded into scaffolds using pectin (PECT) as a carrier. Osteochondral defects in medial femoral condyles of rabbits were created and randomly allocated in one of the following groups: plain scaffold (PU/VAC), scaffold with hAMSCs injected in the implant site (PU/VAC/hAMSC), scaffold with hAMSCs loaded in pectin (PU/VAC/PECT/hAMSC), and no treated defects (untreated). The therapeutic efficacy was assessed by macroscopic, histological, histomorphometric, microtomographic, and ultrastructural analyses at 3, 6, 12, and 24 weeks. Histological results showed that the scaffold was permissive to tissue growth and penetration, an immature osteocartilaginous tissue was observed at early experimental times, with a more accentuated bone regeneration in comparison with the cartilage layer in the absence of any inflammatory reaction. Abstract : To address the unsolved clinical need of regeneration of osteochondral lesions, Tschon and coworkers developed a new 3D scaffold made of porous polyurethane foam, coated with calcium phosphates. Human amniotic mesenchymal stromal cells were chosen as innovative source of mesenchymal stem cells and loaded in the scaffold using pectin gel as a carrier. Biocompatibility and biofunctionality were assessed after implantation in an in vivo rabbit osteochondral model by macroscopic, histological, histomorphometric, microtomographic and ultrastructural analyses.